APLIKASI SISTEM PENDUKUNG KEPUTUSAN PEREKRUTAN CALON PEGAWAI NEGERI SIPIL (CPNS) DI KEMENTERIAN PERDAGANGAN RI PADA TES KOMPETENSI BIDANG (TKB) DENGAN - Rahma Farah Ningrum (PETIR, 2015)
Designing an application decision support system using ANP (Analytical Network Process) atthis stage of recruitment of civil servants is not easy, should be aligned with the procedures thathave been set by national civil servant recruitment committee or department. Stages selectingemployess that will register as an employee in the Ministry of Trade consists of administrativeselection Basic Competence Test (TKD), and Competency Test Field (TKB). To produce a validscreening employees, required measurable decision-making based on the results of theamalgamation of several existing tests. To design the application in writing is done with thewaterfall method by combining the methods of ANP (Analytical Network Process) as measurementdata validity of the tests conducted. Methods ANP (Analytical Network Procees) to represent thedegree of importance some of the results of tests conducted by considering the relationship betweenthe criteria. ANP (Analytical Network Process) combines some of the assessments into one logicalway. And the results obtained from this screening is a candidate for employee data sorting used asan alternative in the decision so that the recruitment process can take place effectively andefficiently and to produce objective decisions.